Inhibition of mTOR or MAPK ameliorates vmhcl/myh7 cardiomyopathy in zebrafish - Bu, Haisong; Ding, Yonghe; Li, Jiarong; Zhu, Ping; Shih, Yu-Huan; Wang, Mingmin; Zhang, Yuji; Lin, Xueying; Xu, Xiaolei (JCI insight, 2021)
Myosin heavy chain 7 (MYH7) is a major causative gene for hypertrophic cardiomyopathy, but the affected signaling pathways and therapeutics remain elusive. In this research, we identified ventricle myosin heavy chain like (vmhcl) as a zebrafish homolog of human MYH7, and we generated vmhcl frameshift mutants. We noted vmhcl-based embryonic cardiac dysfunction (VEC) in the vmhcl homozygous mutants and vmhcl-based adult cardiomyopathy (VAC) phenotypes in the vmhcl heterozygous mutants. Using the VEC model, we assessed 7 known cardiomyopathy signaling pathways pharmacologically and 11 candidate genes genetically via CRISPR/Cas9 genome editing technology based on microhomology-mediated end joining (MMEJ). Both studies converged on therapeutic benefits of mTOR or mitogen-activated protein kinase (MAPK) inhibition of VEC. While mTOR inhibition rescued the enlarged nuclear size of cardiomyocytes, MAPK inhibition restored the prolonged cell shape in the VEC model. The therapeutic effects of mTOR and MAPK inhibition were later validated in the VAC model. Together, vmhcl/myh7 loss of function is sufficient to induce cardiomyopathy in zebrafish. The VEC and VAC models in zebrafish are amenable to both efficient genetic and chemical genetic tools, offering a rapid in vivo platform for discovering candidate signaling pathways of MYH7 cardiomyopathy.